Exploring COVID-19 Vaccine’s Adverse Event Following Immunization on educational staff at the Faculty of Medicine - Muthmainah, Noor; Skripsiana, Nika Sterina; Aprilia, Gita Rizky; Rahmiati, Rahmiati; Yuniarti, Rina (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2025)
Background: COVID-19 was declared a global pandemic on March 11, 2020. Vaccination is one of the efforts to prevent and treat COVID-19. One thing that needs to be considered in the COVID-19 vaccination is the emergence of Adverse Event Following Immunization (AEFI). The reactions after vaccination can be local, systemic, or other.Objective: This study aimed to depict the AEFI of the COVID-19 vaccine on educational staff, Faculty of Medicine, ULMMethods: This study was a retrospective descriptive study with a cross-sectional approach using primary data in the form of a questionnaire given directly to the respondents. This research was conducted in October-November 2022 at the Faculty of Medicine, ULM.Results: The results showed that 84.4% of the respondents experienced AEFI in the first vaccination dose.  The AEFIs were most experienced by groups of 41-50 years (36.84%), females (65.79%), S1 (55.26%), and the Sinovac vaccine type (84.21%). Besides, for the second dose, 77.8% respondents experienced AEFI. Most AEFIs were experienced by the group of 20-30, 31-40, and 41-50 years (31.43%), female (71.43%), S1 (57.14%), and the Sinovac vaccine type (80%). The most common symptom was pain at the injection area (48.89%). The onset was most often on the first day (48.89%), and it took 1-2 days, with 35.5% as the response to the first dose and 26.6% for the second dose.Conclusion: Most of the AEFIs in the first vaccination dose were experienced by the 41-50-year-old group. Meanwhile, the second vaccination dose was administered to groups of 20-30, 31-40, and 41-50. The AEFI occurred most often in females, S1, and the Sinovac vaccine type. The most common AEFI symptom was pain at the injection site, followed by drowsiness and fatigue. The most AEFI cases were on the first day, and the duration was 1-2 days.